Analisis Regresi Locus Of Control dan Kemampuan Mengumpulkan Informasi Karir Terhadap Kencenderungan Siswa Menggunakan Intuisi dalam Resiliensi Karir Era Postmodern - Nanda Alfan Kurniawan; Randi Saputra; Reza Artamevia Kusuma Wardan (Proceedings Series of Educational Studies, 2023)
Career resilience in the postmodern era is the key for vocational school students in maintaining personal existence and social identity. This research aims to explore the influence of locus of control and the ability to gather information on students' tendency to use intuition in career resilience in vocational schools. The research method uses quantitative with a non-experimental design. The data collection technique uses purposive random sampling by paying attention to the criteria of class, gender and student residence. The research subjects were determined to be 531 students (class X), 456 (class XI), and 56 (class Parametric data analysis techniques use mediation analysis or multiple regression. The research results show that Locus of Control and the Tendency to use intuition have a positive correlation of 0.470, while the ability to gather information has a negative correlation of -0.046. The research conclusions show that the ability to gather career information can influence the locus of control and achieve intuition so that career resilience is maintained. It is recommended that future research explore forms of postmodern counseling interventions that can increase vocational school students' career resilience